2022
DOI: 10.1021/acs.analchem.1c04456
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Aptasensors Based on Electrochemical Impedance Spectroscopy and Low-Cost Gold Electrode Substrates

Abstract: SARS-CoV-2 diagnostic practices broadly involve either quantitative polymerase chain reaction (qPCR)-based nucleic amplification of viral sequences or antigen-based tests such as lateral flow assays (LFAs). Reverse transcriptase-qPCR can detect viral RNA and is the gold standard for sensitivity. However, the technique is time-consuming and requires expensive laboratory infrastructure and trained staff. LFAs are lower in cost and near real time, and because they are antigen-based, they have the potential to pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
(58 reference statements)
1
28
0
1
Order By: Relevance
“…Using Optimer (optimized aptamers) ligands and mass-fabricated thin-film gold electrode (TFGE) sensors, Lasserre et al reported an impedimetric, low-cost, high-specificity mass testing platform for SARS-CoV-2 S1 protein detection in 15 min [102]. The SARS-CoV-2 S1 domain-specific DNA Optimer was synthesized from a pool of 10 14 sequences, while the TFGE was made using an inexpensive glucose test strip material (i.e., polyester substrate).…”
Section: Chip-based Electrochemical Antigen Detectionmentioning
confidence: 99%
“…Using Optimer (optimized aptamers) ligands and mass-fabricated thin-film gold electrode (TFGE) sensors, Lasserre et al reported an impedimetric, low-cost, high-specificity mass testing platform for SARS-CoV-2 S1 protein detection in 15 min [102]. The SARS-CoV-2 S1 domain-specific DNA Optimer was synthesized from a pool of 10 14 sequences, while the TFGE was made using an inexpensive glucose test strip material (i.e., polyester substrate).…”
Section: Chip-based Electrochemical Antigen Detectionmentioning
confidence: 99%
“…Accordingly, the sensor could detect SP within 15 min with a LOD of 64 fM in COVID-19 patient's nasopharyngeal samples. Other works related to the use of antibodies, aptamers, ACE2, and MIPs as receptors for electrochemical detection of SARS-CoV-2 SP [80][81][82][83][84][85][86] and their analytical performances are summarized in Table 3.…”
Section: Detection Of Spike Proteinsmentioning
confidence: 99%
“…Similarly to MIP-based sensors, also virus-imprinted sensors have been realized for detection of several viruses [58] , [59] , [60] . Hussein et al [61] constructed the first impedimetric nanosensor based on a screen-printed carbon electrode modified with carbon nanotubes/tungsten oxide (CNTs/WO 3 ) for imprinting the complete SARS-CoV-2 particles within the polymer to create virus complementary binding sites.…”
Section: Electrochemical Biosensors For Covid-19mentioning
confidence: 99%